Preparation Of Cotton Raw Material And Analys Of Its Acceptance And Delivery Mechanisms (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article describes about  the period of cotton harvest at the ginnery under the Aktash ginnery No. 3 in the system of cotton-textile cluster and the periodic delivery of cotton on the day of delivery of the maximum amount of cotton in the season, the receipt of cotton delivered by truck to ginneries. and taking into account the status of domestic and foreign transporters used in the transmission, 20-30% of the total amount of cotton to be accepted at the enterprise, 70-80% in the outlying areas, the current XPP-III transporter receives and transfers cotton due to low productivity cases of non-compliance with the requirements of the technological process.Object of the work:One of the main requirements for the technological process of cotton processing today is to improve the performance of the XPP-III cotton receiving and transfer conveyor while maintaining the natural properties of the raw material.Methods: Due to the large amount of cotton in the horizontal belt on the XPP-III conveyor and the increase in the mass of cotton, it was observed that the cotton is fed to the sloping belt elevator in a dense and large amount without crushing.Results: It was studied that the process of entering a large amount of cotton into the settlement should be between 18:00 and 22:00 hours, and during this time all the mechanized means in the settlement should work at high productivity.Conclusion: operation of all machinery at high voltage as a result of continuous supply of cotton to the cotton mill,their time to unload cotton from trucks,non-accumulation of vehicles,it will be necessary to avoid congestion from waiting traffic,  and  all this shows the need of creating a machine that receives and transmits cotton which operates at high productivity.